TOKSISITAS AKUT BANDOTAN (Ageratum conyzoides ) TERHADAP MORTALITAS KUMBANG JAGUNG (Sitophilus zeamais Motschulsky) - Ita Emilia, Dian Mutiara (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2013)
Investigation about Acut Â Toxicity ofÂ  Â Bandotan Leaf ( Ageratum conyzoides) Â to Mortality Maize Weevil (Sitophilus zeamays) was conducted on Juni â September 2013 in laboratory Biology Faculty of MathematicÂ  University of PGRI Palembang. Acut tocxicityÂ  test using the maize weveilÂ  bioassay method with a time of 96 hours aplication. The shows that results that leaf of Bandotan were toxic to maize weevil whith Â 24 hours, 48 hours and Â 96 hours LC 50 were Â Â 29.279 %, 21.610 % Â and Â Â 16.477 Â %.Â Key words ; Â Â Toxicity. Ageratum conyzoides,Â Â  Sitophilus zeamais M.). Â Â LC50